Tibetan Monastics Reflect on Science and Buddhism: (I) The Basic Human Nature and (II) Subatomic Particles - Gyaltsen, Jampa; Gyatso, Lobsang; Drongbu, Dawa Tsering (Frontiers in Communication, 2021)
One of the goals of the historic Emory-Tibet Science Initiative (ETSI) is to catalyze cross-cultural thinking among scientists and Buddhists. Over a decade into the project to elicit such thinking the project sponsored an essay competition among the monastics. Here we feature two of the winners reflecting on different aspects of western sciences and Buddhism, physics and Buddhism respectively, demonstrating how modern science is integrating with the monastics’ traditional training and culture. A key aspect of ETSI is also translation, and these essays, in that spirit were translated from Tibetan to English by one of the project translators.